2020
DOI: 10.1155/2020/9201967
|View full text |Cite
|
Sign up to set email alerts
|

Quo Vadis PCA? A Review on Current Concepts, Economic Considerations, Patient-Related Aspects, and Future Development with respect to Patient-Controlled Analgesia

Abstract: This review assesses four interrelating aspects of patient-controlled analgesia (PCA), a long-standing and still widely used concept for postoperative pain management. Over the years, anaesthesiologists and patients have appreciated the benefits of PCA alike. The market has seen new technologies leveraging noninvasive routes of administration and, thus, further increasing patient and staff satisfaction as well as promoting safety aspects. Pharmaceutical research focuses on the reduction or avoidance of opioids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
3
0
2
Order By: Relevance
“…Third, figures vary because of analgesic technique. Studies have confirmed that the application of PCIA could greatly improve the level of post-operative acute pain management (Kikuchi et al, 2019;Nardi-Hiebl et al, 2020). In this study, PCIA was used to control post-operative pain in most patients (82.10%).…”
Section: Status Of Post-operative Inadequate Pain Control In Patients...mentioning
confidence: 59%
“…Third, figures vary because of analgesic technique. Studies have confirmed that the application of PCIA could greatly improve the level of post-operative acute pain management (Kikuchi et al, 2019;Nardi-Hiebl et al, 2020). In this study, PCIA was used to control post-operative pain in most patients (82.10%).…”
Section: Status Of Post-operative Inadequate Pain Control In Patients...mentioning
confidence: 59%
“…Patient-controlled analgesia (PCA) is a technique that allows patients to self-administer medication within predetermined limits as needed. It is currently a more mature semi-closed-loop intravenous drug delivery method 56 . It integrates real-time monitoring equipment and feedback modules, which can automatically adjust drug doses based on patient feedback or vital signs.…”
Section: Future Development Trendsmentioning
confidence: 99%
“…El inadecuado control del dolor en el paciente en general y especialmente del postquirúrgico está sobre la mesa en distintos centros sanitarios mundiales (incluyendo a los latinoamericanos desde hace décadas), pese a la implementación en el uso de dispositivos de analgesia controlada por el paciente (PCA) (35) o a la instauración de los primeros estándares y guías como la «Achieving Improved Measurement» del Canadian Council on Health Services Accreditation (36) , o la creación paulatina de unidades especializadas en dolor en cada centro hospitalario (37) . Unidades con instalaciones adecuadas, equipos multidisciplinares (médicos, cirujanos, enfermeros), estrategias propias y recursos de toda índole tales como registros clínicos (38) , nuevas terapias y programas de rehabilitación (39) o grupos de trabajo como PROSPECT (Procedure-Specific Postoperative Pain Management), que brinda a los profesionales de la salud recomendaciones prácticas y específicas por procedimientos para facilitar la toma de decisiones en todas las etapas del período operatorio (40) , también forman parte de los intentos por mejorar el control del dolor en el terreno postoperatorio.…”
Section: Causas Del Pobre Manejo Del Dolor Postoperatorio En Latinoamérica Y Medidas Preventivas Para Minimizar Su Impactounclassified